Engagement and satisfaction: mixed-method analysis of blended learning in the sciences - Lane, Stephen; Hoang, John G.; Leighton, Jacqueline P.; Rissanen, Anna (My University, 2021)
Recent advancements in technology and increased globalization due to the internet have led to the development and popularization of asynchronous teaching formats. One of these is blended learning (BL), which combines online and physically in-person learning. While it is widely agreed that BL formats lead to measurable increases in student performance, little is understood about the relationship between student satisfaction and improved performance. We conducted an analysis of student and instructor feedback collected from surveys and interviews from four science courses converted from physically co-located to BL formats at a Canadian university. We specifically probed students’ experiences of BL, and student satisfaction in the blended format. We find that emotional engagement is a broadly applicable predictor of student satisfaction and success in BL courses. Specifically, we recommend instructors maintain personal connection with students, use collaborative active learning strategies, and emphasize alignment of learning activities with learning objectives. These may enhance the student experience and minimize challenges that have become characteristic of asynchronous teaching formats.
Keywords: blended learning; science education; satisfaction; emotional engagement; cognitive engagement; behavioural engagement